2021
DOI: 10.1007/s10620-020-06797-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Alpha-Fetoprotein in Alpha-Fetoprotein Negative Hepatocellular Carcinoma Underwent Curative Resection

Abstract: Background The clinical value of alpha-fetoprotein (AFP) in patients with AFP-negative (< 20 ng/ml) hepatocellular carcinoma (HCC) who underwent curative resection remained controversial. Aims To investigate clinical relevance and prognostic effect of preoperative serum AFP level in this subgroup. Methods A total of 1879 patients with AFP-negative HCC who underwent curative resection were included in the study. Overall survival (OS) and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“… 26 Even in AFP-negative HCC patients, AFP was still an independent prognostic factor. 6 We also found that AFP was associated with recurrence in AFP-negative HCC patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“… 26 Even in AFP-negative HCC patients, AFP was still an independent prognostic factor. 6 We also found that AFP was associated with recurrence in AFP-negative HCC patients.…”
Section: Discussionsupporting
confidence: 53%
“…2,3 Many serum biomarkers have been used for diagnosis and treatment of HCC. [4][5][6][7] Alpha-fetoprotein (AFP) is the most widely used serum biomarker for HCC in diagnosis and surveillance. 8 Elevated AFP is associated with aggressive tumor features and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Univariate analysis revealed that the significant predictive factors for poorly differentiated HCC were AFP > 20 ng/mL, lens culinaris agglutinin‐reactive fraction of alpha‐fetoprotein (AFP‐L3) ≥ 10%, DCP ≥ 100 mAU/mL, tumor size ≥ 50 mm, microvascular invasion, intrahepatic metastasis, and SIRPP ≤ 0.85. We defined the SIRPP cutoff level using ROC analysis and the cutoff levels of AFP and DCP, according to previous reports 13,14 . Multivariate analysis revealed that the independent predictive factors for poorly differentiated HCC were AFP > 20 ng/mL (hazard ratio [HR]: 3.23, 95% confidence interval [CI]: 1.39–7.47, p = .0065) and SIRPP ≤ 0.85 (HR: 4.44, 95% CI: 1.9–10.4, p = .0006) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We defined the SIRPP cutoff level using ROC analysis and the cutoff levels of AFP and DCP, according to previous reports. 13,14 Multivariate analysis revealed that the independent predictive factors for poorly differentiated HCC were AFP > 20 ng/mL (hazard ratio [HR]: 3.23, 95% confidence interval [CI]: 1.39-7.47, p = .0065) and SIRPP ≤ 0.85 (HR: 4.44, 95% CI: 1.9-10.4, p = .0006) (Table 1). The rate of poorly differentiated HCC was 64% in the group with AFP > 20 ng/mL and SIRPP ≤ 0.85, 24% in the group with AFP ≤ 20 ng/mL and SIRPP ≤ 0.85, or AFP > 20 ng/mL and SIRPP > 0.85, and 10% in the group with AFP ≤ 20 ng/mL and SIRPP > 0.85.…”
Section: Independent Predictive Factors For Poorly Differentiated Hccmentioning
confidence: 99%
“…Biomarkers such as α-fetoprotein (AFP) are associated with a more aggressive tumour phenotype and higher recurrence risk after surgical resection, while a significant proportion of patients do not present elevation of AFP serum levels [8,9] . About 30-40% of the patients with HCC present low levels (<20 ng/ml) of this biomarker, however, even in these cases AFP levels are correlated with a poorer differentiation of the tumour, microvascular invasion, presence of satellite nodules and disseminated intrahepatic metastasis [9,10] .…”
Section: Introductionmentioning
confidence: 99%